1999
DOI: 10.1152/ajpgi.1999.276.6.g1345
|View full text |Cite
|
Sign up to set email alerts
|

Activation of VEGF and Ras genes in gastric mucosa during angiogenic response to ethanol injury

Abstract: Our previous studies demonstrated that ethanol injury triggers the angiogenic response in gastric mucosa bordering necrosis. The present study was aimed to determine whether vascular endothelial growth factor (VEGF) (a potent angiogenic peptide selectively acting on endothelial cells) and Ras (a mediator of cell proliferation and a putative regulator of VEGF expression) are involved in gastric angiogenesis after ethanol injury. We studied the angiogenic response and expression of VEGF and Ras in gastric mucosa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
59
0
2

Year Published

2000
2000
2018
2018

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 50 publications
(64 citation statements)
references
References 26 publications
3
59
0
2
Order By: Relevance
“…Recently, ethanol has been found to activate the angiogenic stimulator vascular endothelial growth factor through HIF-1␣ and Ras (7,40). It is unclear at this time whether the activation of Cdc42 upon stimulation by ethanol is related to those pathways.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, ethanol has been found to activate the angiogenic stimulator vascular endothelial growth factor through HIF-1␣ and Ras (7,40). It is unclear at this time whether the activation of Cdc42 upon stimulation by ethanol is related to those pathways.…”
Section: Discussionmentioning
confidence: 99%
“…The molecular mechanisms of its pathogenic and protective effects are not fully established. Previous studies indicate that ethanol can induce angiogenesis (7,8). Angiogenesis, the process of forming new blood vessels out of pre-existing capillaries (9), is a sequential event that involves (a) the disintegration of the basement membrane, (b) the migration of endothelial cells, (c) endothelial cell proliferation in cords with formation of new vascular channels, and (d) the formation of a new basement membrane (10).…”
mentioning
confidence: 98%
“…Our previous studies demonstrated that activation of the MAP (Erk-1 and -2) kinase signal transduction pathway and Ras gene is crucial for VEGF-induced stimulation of angiogenesis and that NSAIDs may interfere with angiogenesis by inhibiting MAPK/Erk pathway (32,33).…”
Section: Cellular and Molecular Events In Granulation Tissue: Angiogementioning
confidence: 99%
“…The overexpression of Tie2, Ang1 and Ang2 occurs in early phase of gastric ulcer healing (39,40) and likely stimulates angiogenesis in granulation tissue by the above mechanisms (36). The extracellular-regulated kinases (Erks), which are members of a larger group of mitogen-activated protein kinases (MAPK), are the key components in several signaling pathways involved in angiogenesis, in the activation of transcription factors and early response genes ultimately leading to endothelial cell proliferation and/or differentiation (32,33). Phosphatidylinositol 3-kinase (PI-3K), is another important kinase which has been shown to be activated by most mitogens and has been implicated as a critical factor in the regulation of endothelial cell proliferation, survival and motility (41).…”
Section: Cellular and Molecular Events In Granulation Tissue: Angiogementioning
confidence: 99%
“…On the other hand, in chronic duodenal ulcer VEGF stimulates granulation tissue formation and angiogenesis resulted in ulcer healing. In addition, upregulation of VEGF mRNA expression was observed after ethanol challenge [59].…”
Section: Growth Factorsmentioning
confidence: 96%